(untitled) (Ustozlar uchun, 2025)
In today’s globalized world, proficiency in English is more important than ever. Schools are increasingly recognizing the need for effective English language training that goes beyond traditional classroom instruction. The process of English language practical training in schools encompasses several key components designed to enhance students' language skills through immersive and interactive experiences. This article outlines the essential steps involved in this training process.